دور التحليل المالي في كفاءة الرقابة على الأداء المالي والانحرافات في المصارف: ) دراسة حالة - بنك النيل للتجارة والتنمية الفرع الرئاسي) - د. عبد الرحمن عبد الله كبسور,; د. نشوي عمر محمد خير,; د. أسامة حسين محمد يوسف كبر , (White Nile Journal for Studies and Research, 2019)
The problem of research was the role of financial analysis in determining the efficiency and accuracy of control over financial performance and its reflection in controlling the deviations of banks, which aims to show the concepts of the analysis, its tools, methods and fields. Its importance in achieving and activating supervision, especially the field of banking services, In the use of financial analysis to improve banking institutions and detect the actual and expected deviations. The hypotheses of the research were that there are statistically significant differences between the use of tools and methods, financial analysis and the efficiency of control over financial performance. There are significant differences The results of the research are as follows: The Bank follows the policy of balance between liquidity and profitability and the good utilization of resources and the resulting profits, as evidenced by the impact of financial analysis through (tools, methods, indicators) on efficiency Control of financial performance and control of deviations. The Bank has effective departments and departments to manage risk, liquidity, market risk management, credit risk, investment risk and others. These departments play an active role in the proper direction of good investments, Timely and across the network. The study recommends the need to develop models of measurement and provide advanced banking indicators and provide more studies that deal with raising the profits of banking as well as the need to pay attention to diversification of investment areas that the surplus of liquidity and deposits in the case of investment in government certificates, seminars, lectures and dissemination of role to disseminate the concepts of financial analysis and financial performance.